Thermoplastic polyurethane elastomer material and preparation method thereof
By adding phosphorus-based, nitrogen-based flame retardant, modified polyhedral oligosilsesquioxane and its derivatives to the TPU material, a variety of protective layers are formed, which solves the problem of poor flame retardancy of TPU materials and achieves the improvement of high flame retardant performance and mechanical properties.
Patent Information
- Application Number
- CN202411993271.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The poor flame retardancy of existing TPU materials limits their domestic applications, especially in the context of new energy policies with high flame retardant requirements.
Using thermoplastic polyurethane elastomer material, a variety of protective layers are formed to improve flame retardant performance by adding phosphorus-based flame retardant, nitrogen-based flame retardant, and modified polyhedral oligosilsesquioxane and its derivative flame retardant synergistic agent.
It significantly improves the flame retardant performance of the material, reaches the V0 flame retardant level, and improves the mechanical properties to meet the high flame retardant requirements.
Smart Images

Figure CN119752158A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of materials, and in particular to a thermoplastic polyurethane elastomer material. Background Art
[0002] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.
[0003] Thermoplastic polyurethane elastomers (TPU) are mainly polyester and polyether types. They have a wide hardness range, excellent mechanical properties, wear resistance, oil resistance and excellent elasticity. At present, TPU materials are widely used in shoe materials, pipes, tires, membrane materials and cable materials. There are many kinds of low-smoke and halogen-free flame-retardant TPU cable materials in the foreign market that can meet the flame-retardant requirements of UL wires. The comprehensive performance of low-smoke and halogen-free flame-retardant TPU cable materials produced domestically is still far behind that of imported products. The technical monopoly has led to the high price of imported high-flame-retardant TPU cable materials. With the introduction of new energy policies, my country has also begun to vigorously develop flame-retardant TPU materials, but due to the limitations of domestic flame-retardant technology, the development of high-flame-retardant TPU materials has not made significant progress. This limits the application of TPU in China, so it is very necessary to develop a highly flame-retardant TPU material. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a thermoplastic polyurethane elastomer material, aiming to solve the problem of poor flame retardancy of the current TPU material.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a thermoplastic polyurethane elastomer material, wherein the raw materials of the thermoplastic polyurethane elastomer material, measured in parts by weight, include:
[0007] Thermoplastic polyurethane elastomer 70-90 parts,
[0008] Phosphorus flame retardant 10-30 parts,
[0009] 10-30 parts of nitrogen flame retardant,
[0010] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,
[0011] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:
[0012]
[0013] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;
[0014] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0015] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;
[0016] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
[0017] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:
[0018]
[0019] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.
[0020] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:
[0021] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;
[0022] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;
[0023] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
[0024] In some embodiments of the present invention, the raw materials of the thermoplastic polyurethane elastomer material include, by weight:
[0025] Thermoplastic polyurethane elastomer 70-90 parts,
[0026] Phosphorus flame retardant 10-20 parts,
[0027] 10-20 parts of nitrogen flame retardant,
[0028] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.
[0029] In some embodiments of the present invention, the thermoplastic polyurethane elastomer includes a polyether type or polyester type thermoplastic polyurethane elastomer.
[0030] In some embodiments of the present invention, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide;
[0031] And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.
[0032] In some embodiments of the present invention, the raw materials of the thermoplastic polyurethane elastomer material also include at least one of a lubricant, an antioxidant, an anti-hydrolysis agent, and a matting agent; wherein, the raw materials are calculated by weight, the lubricant is 0.5-1 part, the antioxidant is 0.5-2 parts, the anti-hydrolysis agent is 0.5-2 parts, and the matting agent is 2-10 parts.
[0033] The second aspect of the present invention provides a method for preparing the above-mentioned thermoplastic polyurethane elastomer material, comprising the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder to obtain granular material, namely the thermoplastic polyurethane elastomer material.
[0034] In some embodiments of the present invention, the raw material further comprises at least one of a lubricant, an antioxidant, an anti-hydrolysis agent, and a matting agent;
[0035] And / or, the extruder is a twin-screw extruder, the extrusion temperature is 160-180° C., and the screw speed is 150-170 r / min.
[0036] The thermoplastic polyurethane elastomer material of the invention comprises thermoplastic polyurethane elastomer, phosphorus-based flame retardant, nitrogen-based flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source and the nitrogen flame retardant providing the gas source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant properties and mechanical properties of the thermoplastic polyurethane elastomer material. The thermoplastic polyurethane elastomer material provided by the present invention has excellent flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;
[0038] Figure 2 This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0040] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0041] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.
[0042] Thermoplastic polyurethane elastomers (TPU) are mainly polyester and polyether types. They have a wide hardness range, excellent mechanical properties, wear resistance, oil resistance and excellent elasticity. At present, TPU materials are widely used in shoe materials, pipes, tires, membrane materials and cable materials. There are many kinds of low-smoke and halogen-free flame-retardant TPU cable materials in the foreign market that can meet the flame-retardant requirements of UL wires. The comprehensive performance of low-smoke and halogen-free flame-retardant TPU cable materials produced domestically is still far behind that of imported products. The technical monopoly has led to the high price of imported high-flame-retardant TPU cable materials. With the introduction of new energy policies, my country has also begun to vigorously develop flame-retardant TPU materials, but due to the limitations of domestic flame-retardant technology, the development of high-flame-retardant TPU materials has not made significant progress. This limits the application of TPU in China, so it is very necessary to develop a highly flame-retardant TPU material.
[0043] In order to solve the above problems, the first aspect of the present invention provides a thermoplastic polyurethane elastomer material, wherein the raw materials of the thermoplastic polyurethane elastomer material, measured in parts by weight, include:
[0044] Thermoplastic polyurethane elastomer 70-90 parts,
[0045] Phosphorus flame retardant 10-30 parts,
[0046] 10-30 parts of nitrogen flame retardant,
[0047] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,
[0048] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:
[0049]
[0050] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;
[0051] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0052] It can be understood that the thermoplastic polyurethane elastomer is any number between 70-90 parts, such as 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, etc.; the phosphorus-based flame retardant is any number between 10-30 parts, such as 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, etc.; the nitrogen-based flame retardant is any number between 10-30 parts, such as 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, etc.; the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is any number between 2-8 parts, such as 2 parts, 4 parts, 6 parts, 8 parts, etc.
[0053] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.
[0054] It is understandable that phosphorus-based flame retardants decompose to form a non-flammable liquid film of phosphoric acid during combustion. At the same time, phosphoric acid is further dehydrated to form metaphosphoric acid, which is further polymerized to form polymetaphosphoric acid. In this process, not only does the covering layer generated by phosphoric acid have a covering effect, but also because the generated polymetaphosphoric acid is a strong acid and a strong dehydrating agent, it dehydrates the polymer and carbonizes it, changing the mode of the polymer combustion process and forming a carbon film on its surface to isolate the air, thereby exerting a stronger flame retardant effect. At the same time, phosphorus-based flame retardants are also a free radical scavenger. Using mass spectrometry technology, it is found that any phosphorus-containing compound forms PO· when the polymer burns. It can combine with hydrogen atoms in the flame area to suppress the flame. In addition, the moisture produced by phosphorus-based flame retardants during the flame retardant process can, on the one hand, reduce the temperature of the condensed phase, and on the other hand, dilute the concentration of combustibles in the gas phase, thereby better playing a flame retardant role. Nitrogen-based flame retardants decompose at high temperatures to produce non-combustible gases such as ammonia, water vapor, and nitrogen. These gases can dilute the concentration of combustibles in the gas phase and inhibit combustion. The two work synergistically in the condensed phase and gas phase to increase the carbonization rate, form a more stable and uniform carbon layer, and improve the flame retardant effect. The boron element in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gases and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent heat transfer, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. The modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant contain a large amount of silicon and oxygen elements. During the combustion of the polymer, they form phosphates with the acidic gas after the combustion of the phosphorus flame retardant, which promotes the reaction between the phosphorus element and the polymer, thereby quickly forming a carbon layer. The SiO2 generated by the combustion of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant 2Interspersed in the coke layer, similar to the role of sand in cement, the coke layer is more stable. The coke layer makes it difficult for heat to penetrate the condensed phase, preventing oxygen from entering the combustion area and the gaseous or liquid products generated by degradation from overflowing the surface of the material. The boron in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital that can accept lone pairs of electrons and can produce a synergistic effect when coordinated with phosphorus. The synergistic effect of boron and phosphorus makes the above reaction faster. At the same time, the combustion of nitrogen-based flame retardants produces a large amount of non-combustible gas, which causes the system in the molten state of the incompletely carbonized part of TPU to foam, causing the burning polymer to produce a large number of pores. At the same time, the organic matter continues to react, dehydrate and carbonize to form inorganic matter and carbon residues. When the reaction is completed, the system gels and solidifies, and finally forms a porous foam carbon layer.
[0055] The thermoplastic polyurethane elastomer material of the invention comprises thermoplastic polyurethane elastomer, phosphorus-based flame retardant, nitrogen-based flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source and the nitrogen flame retardant providing the gas source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant properties and mechanical properties of the thermoplastic polyurethane elastomer material. The thermoplastic polyurethane elastomer material provided by the present invention has excellent flame retardant properties.
[0056] In some embodiments, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.
[0057] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.
[0058] In some embodiments, R2 is a benzofuranyl group.
[0059] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.
[0060] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.
[0061] In some embodiments, R2 is a naphthyl ring group.
[0062] In some embodiments, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:
[0063]
[0064] In some embodiments, the molar ratio of compound 1 to compound 2 during the above reaction is 2:1.
[0065] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.
[0066] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.
[0067] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.
[0068] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.
[0069] In some embodiments, compound 2 is dibenzofuran-3-boronic acid.
[0070] In some embodiments, the structural formula of compound 3 is:
[0071]
[0072] The following is designated as modified POSS flame retardant synergist 1.
[0073] In some embodiments, the structural formula of compound 3 is:
[0074]
[0075] The following is designated as modified POSS flame retardant synergist 2.
[0076] In some embodiments, the preparation method of compound 3 comprises the following steps:
[0077] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;
[0078] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;
[0079] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
[0080] In some embodiments, the catalyst is acetic acid.
[0081] In some embodiments, the solvent is ethanol.
[0082] In some embodiments, the raw materials of the thermoplastic polyurethane elastomer material include, by weight:
[0083] Thermoplastic polyurethane elastomer 70-90 parts,
[0084] Phosphorus flame retardant 10-20 parts,
[0085] 10-20 parts of nitrogen flame retardant,
[0086] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.
[0087] Reducing the amount of phosphorus-based flame retardants and nitrogen-based flame retardants can further improve the mechanical properties of thermoplastic polyurethane elastomer materials.
[0088] In some embodiments, the thermoplastic polyurethane elastomer includes a polyether-type or polyester-type thermoplastic polyurethane elastomer.
[0089] In some embodiments, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide flame retardant;
[0090] And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.
[0091] It is understood that the phosphorus-based flame retardants include, but are not limited to, aluminum hypophosphite, calcium hypophosphite, diethyl aluminum hypophosphite, methylethyl aluminum hypophosphite and phenyl aluminum hypophosphite.
[0092] In some embodiments, the phosphorus-based flame retardant is diethyl aluminum phosphite.
[0093] In some embodiments, the nitrogen-based flame retardant is melamine urate.
[0094] In some embodiments, the raw materials of the thermoplastic polyurethane elastomer material also include at least one of a lubricant, an antioxidant, an anti-hydrolysis agent, and a matting agent; wherein, the raw materials are calculated in parts by weight, and the lubricant is 0.5-1 part, the antioxidant is 0.5-2 parts, the anti-hydrolysis agent is 0.5-2 parts, and the matting agent is 2-10 parts.
[0095] In some embodiments, the antioxidant includes, but is not limited to, asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants.
[0096] Hindered phenol antioxidants include, but are not limited to, antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), BHT (2,6-di-tert-butyl-p-cresol), and antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate);
[0097] Aromatic amine antioxidants include, but are not limited to, diphenylamine, p-phenylenediamine, and dihydroquinoline and their derivatives or polymers, such as: Antioxidant 445 (4,4'-bis(α.α-dimethylbenzyl)diphenylamine);
[0098] Thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearyl thiodipropionate), and DSTP (octadecyl thiodipropionate);
[0099] Phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol distearyl diphosphite), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite).
[0100] By adding antioxidants, the anti-oxidation and anti-aging properties of polymer materials are improved, and the service life of polymer materials is extended.
[0101] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding the lubricant, it is beneficial to promote a more uniform mixing of various raw materials, improve the fluidity of the polymer resin, reduce the friction coefficient, make the surface of the product smoother, improve the processing efficiency, and improve the transparency and gloss of the plastic.
[0102] In some embodiments, the anti-hydrolysis agent includes, but is not limited to, carbodiimide anti-hydrolysis stabilizers, isocyanates, epoxies, oxazolines and anhydrides, polyethers, polyesters, polyurethanes, polyamides and polyetheresters. By adding an anti-hydrolysis agent, the hydrolysis reaction can be prevented, the processing properties and mechanical properties of the polymer can be improved, and the service life and effect of the polymer can be extended.
[0103] In some embodiments, the matting agent includes an inorganic matting agent and an organic matting agent, wherein the inorganic matting agent includes but is not limited to silicon dioxide, aluminum oxide, and calcium carbonate, and the organic matting agent includes but is not limited to metal soap, wax, diatomaceous earth, and synthetic silicon dioxide. By adding a matting agent, the roughness of the polymer surface can be changed, the gloss of the surface can be reduced, thereby reducing light reflection and making the polymer gloss soft.
[0104] In a second aspect, the present invention provides a method for preparing the above-mentioned thermoplastic polyurethane elastomer material, comprising the following steps: uniformly mixing the raw materials, namely, thermoplastic polyurethane elastomer, phosphorus-based flame retardant, nitrogen-based flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, extruding and granulating through an extruder to obtain a granular material, namely, the thermoplastic polyurethane elastomer material.
[0105] In some embodiments, the raw material further comprises at least one of a lubricant, an antioxidant, an anti-hydrolysis agent, and a matting agent;
[0106] And / or, the extruder is a twin-screw extruder, the extrusion temperature is 160-180° C., and the screw speed is 150-170 r / min.
[0107] The content of the present invention is explained below through specific examples and data.
[0108] The information of the raw materials involved in the specific implementation is shown in Table 1:
[0109] Table 1 Information of raw materials of Examples and Comparative Examples
[0110]
[0111]
[0112] Preparation method of modified POSS flame retardant synergist 1
[0113] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 1.
[0114] Preparation method of modified POSS flame retardant synergist 2
[0115] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain dibenzofuran-3-boric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 2.
[0116] Preparation method of modified POSS flame retardant synergist 3
[0117] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain methylboric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 3.
[0118] Preparation method of modified POSS flame retardant synergist 4
[0119] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain phenylboronic acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 4.
[0120] Embodiment 1:
[0121] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0122] Polyether TPU 90 parts;
[0123] 10 parts of diethyl aluminum hypophosphite;
[0124] 10 parts of melamine urate;
[0125] 15 parts of modified POSS flame retardant synergist;
[0126] PE wax 0.5 parts;
[0127] Antioxidant 10100.5 parts;
[0128] 1 part of carbodiimide;
[0129] 5 parts of silicon dioxide;
[0130] The preparation method is:
[0131] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0132] Embodiment 2:
[0133] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0134] Polyether TPU 70 parts;
[0135] 15 parts of diethyl aluminum hypophosphite;
[0136] 10 parts of melamine urate;
[0137] 18 parts of modified POSS flame retardant synergist;
[0138] PE wax 0.5 parts;
[0139] Antioxidant 10100.5 parts;
[0140] 1 part of carbodiimide;
[0141] 5 parts of silicon dioxide;
[0142] The preparation method is:
[0143] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0144] Embodiment 3:
[0145] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0146] Polyether TPU 90 parts;
[0147] 10 parts of diethyl aluminum hypophosphite;
[0148] 30 parts of melamine urate;
[0149] 12 parts of modified POSS flame retardant synergist;
[0150] PE wax 0.5 parts;
[0151] Antioxidant 10100.5 parts;
[0152] 1 part of carbodiimide;
[0153] 5 parts of silicon dioxide;
[0154] The preparation method is:
[0155] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0156] Embodiment 4:
[0157] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0158] Polyether TPU 80 parts;
[0159] 30 parts of diethyl aluminum hypophosphite;
[0160] 22 parts of melamine urate;
[0161] 15 parts of modified POSS flame retardant synergist;
[0162] PE wax 0.5 parts;
[0163] Antioxidant 10100.5 parts;
[0164] 1 part of carbodiimide;
[0165] 5 parts of silicon dioxide;
[0166] The preparation method is:
[0167] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0168] Embodiment 5:
[0169] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0170] Polyether TPU 90 parts;
[0171] 20 parts of diethyl aluminum hypophosphite;
[0172] 20 parts of melamine urate;
[0173] 18 parts of modified POSS flame retardant synergist;
[0174] PE wax 0.5 parts;
[0175] Antioxidant 10100.5 parts;
[0176] 1 part of carbodiimide;
[0177] 5 parts of silicon dioxide;
[0178] The preparation method is:
[0179] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0180] Embodiment 6:
[0181] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0182] Polyether TPU 70 parts;
[0183] 20 parts of diethyl aluminum hypophosphite;
[0184] 20 parts of melamine urate;
[0185] 18 parts of modified POSS flame retardant synergist;
[0186] PE wax 0.5 parts;
[0187] Antioxidant 10100.5 parts;
[0188] 1 part of carbodiimide;
[0189] 5 parts of silicon dioxide;
[0190] The preparation method is:
[0191] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0192] Embodiment 7:
[0193] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0194] Polyether TPU 80 parts;
[0195] 15 parts of diethyl aluminum hypophosphite;
[0196] 15 parts of melamine urate;
[0197] 15 parts of modified POSS flame retardant synergist;
[0198] PE wax 0.5 parts;
[0199] Antioxidant 10100.5 parts;
[0200] 1 part of carbodiimide;
[0201] 5 parts of silicon dioxide;
[0202] The preparation method is:
[0203] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0204] Embodiment 8:
[0205] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0206] Polyester TPU 80 parts;
[0207] 15 parts of diethyl aluminum hypophosphite;
[0208] 15 parts of melamine urate;
[0209] 15 parts of modified POSS flame retardant synergist;
[0210] PE wax 0.5 parts;
[0211] Antioxidant 10100.5 parts;
[0212] 1 part of carbodiimide;
[0213] 5 parts of silicon dioxide;
[0214] The preparation method is:
[0215] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0216] Embodiment 9:
[0217] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:
[0218] Polyether TPU 80 parts;
[0219] 15 parts of diethyl aluminum hypophosphite;
[0220] 15 parts of melamine urate;
[0221] 25 parts of modified POSS flame retardant synergist;
[0222] PE wax 0.5 parts;
[0223] Antioxidant 10100.5 parts;
[0224] 1 part of carbodiimide;
[0225] 5 parts of silicon dioxide;
[0226] The preparation method is:
[0227] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 1:
[0228] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0229] Polyether TPU 80 parts;
[0230] 10 parts of diethyl aluminum hypophosphite;
[0231] 15 parts of melamine urate;
[0232] 110 parts of modified POSS flame retardant synergist;
[0233] PE wax 0.5 parts;
[0234] Antioxidant 10100.5 parts;
[0235] 1 part of carbodiimide;
[0236] 5 parts of silicon dioxide;
[0237] The preparation method is:
[0238] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 2:
[0239] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0240] Polyether TPU 80 parts;
[0241] 20 parts of diethyl aluminum hypophosphite;
[0242] 15 parts of melamine urate;
[0243] PE wax 0.5 parts;
[0244] Antioxidant 10100.5 parts;
[0245] 1 part of carbodiimide;
[0246] 5 parts of silicon dioxide;
[0247] The preparation method is:
[0248] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 3:
[0249] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0250] Polyether TPU 80 parts;
[0251] 30 parts of melamine urate;
[0252] 15 parts of modified POSS flame retardant synergist;
[0253] PE wax 0.5 parts;
[0254] Antioxidant 10100.5 parts;
[0255] 1 part of carbodiimide;
[0256] 5 parts of silicon dioxide;
[0257] The preparation method is:
[0258] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 4:
[0259] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0260] Polyether TPU 80 parts;
[0261] 30 parts of diethyl aluminum hypophosphite;
[0262] 15 parts of modified POSS flame retardant synergist;
[0263] PE wax 0.5 parts;
[0264] Antioxidant 10100.5 parts;
[0265] 1 part of carbodiimide;
[0266] 5 parts of silicon dioxide;
[0267] The preparation method is:
[0268] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 5:
[0269] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0270] Polyether TPU 80 parts;
[0271] 135 parts of modified POSS flame retardant synergist;
[0272] PE wax 0.5 parts;
[0273] Antioxidant 10100.5 parts;
[0274] 1 part of carbodiimide;
[0275] 5 parts of silicon dioxide;
[0276] The preparation method is:
[0277] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 6:
[0278] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0279] Polyether TPU 80 parts;
[0280] 35 parts of diethyl aluminum hypophosphite;
[0281] PE wax 0.5 parts;
[0282] Antioxidant 10100.5 parts;
[0283] 1 part of carbodiimide;
[0284] 5 parts of silicon dioxide;
[0285] The preparation method is:
[0286] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 7:
[0287] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0288] Polyether TPU 80 parts;
[0289] 35 parts of melamine urate;
[0290] PE wax 0.5 parts;
[0291] Antioxidant 10100.5 parts;
[0292] 1 part of carbodiimide;
[0293] 5 parts of silicon dioxide;
[0294] The preparation method is:
[0295] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 8:
[0296] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0297] Polyether TPU 80 parts;
[0298] 15 parts of diethyl aluminum hypophosphite;
[0299] 15 parts of melamine urate;
[0300] 5 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;
[0301] PE wax 0.5 parts;
[0302] Antioxidant 10100.5 parts;
[0303] 1 part of carbodiimide;
[0304] 5 parts of silicon dioxide;
[0305] The preparation method is:
[0306] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 9:
[0307] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0308] Polyether TPU 80 parts;
[0309] 15 parts of diethyl aluminum hypophosphite;
[0310] 15 parts of melamine urate;
[0311] 5 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;
[0312] PE wax 0.5 parts;
[0313] Antioxidant 10100.5 parts;
[0314] 1 part of carbodiimide;
[0315] 5 parts of silicon dioxide;
[0316] The preparation method is:
[0317] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 10:
[0318] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0319] Polyether TPU 80 parts;
[0320] 15 parts of diethyl aluminum hypophosphite;
[0321] 15 parts of melamine urate;
[0322] 1.6 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;
[0323] 3.4 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;
[0324] PE wax 0.5 parts;
[0325] Antioxidant 10100.5 parts;
[0326] 1 part of carbodiimide;
[0327] 5 parts of silicon dioxide;
[0328] The preparation method is:
[0329] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 11:
[0330] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0331] Polyether TPU 80 parts;
[0332] 15 parts of diethyl aluminum hypophosphite;
[0333] 15 parts of melamine urate;
[0334] 35 parts of modified POSS flame retardant synergist;
[0335] PE wax 0.5 parts;
[0336] Antioxidant 10100.5 parts;
[0337] 1 part of carbodiimide;
[0338] 5 parts of silicon dioxide;
[0339] The preparation method is:
[0340] The above raw materials were weighed according to weight, mixed in a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material. Comparative Example 12:
[0341] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:
[0342] Polyether TPU 80 parts;
[0343] 15 parts of diethyl aluminum hypophosphite;
[0344] 15 parts of melamine urate;
[0345] 45 parts of modified POSS flame retardant synergist;
[0346] PE wax 0.5 parts;
[0347] Antioxidant 10100.5 parts;
[0348] 1 part of carbodiimide;
[0349] 5 parts of silicon dioxide;
[0350] The preparation method is:
[0351] The above raw materials were weighed according to weight, mixed with a high-speed mixer, and then fed into a twin-screw granulator for extrusion granulation at 170° C. and a screw speed of 160 r / min to obtain a thermoplastic polyurethane elastomer material.
[0352] The thermoplastic polyurethane elastomer materials obtained in the above examples and comparative examples were injection molded or molded, and flame retardant grade, oxygen index, tensile strength, elongation at break, 110°C heat shock, 130°C heat shock, 150°C heat shock tests were performed. The test standards are as follows:
[0353] (1) Flame retardant grade
[0354] The test was conducted according to the UL94 standard, with a sample thickness of 3 mm and a test temperature of 23 ± 2 ° C. Three samples were tested using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd., and any dripping was observed.
[0355] (2) Oxygen index
[0356] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The oxygen index of three samples is tested using the oxygen index tester device of Fangshang Analytical Instrument Equipment Factory, Jiangning District, Nanjing, and the results are averaged.
[0357] (3) Tensile strength and elongation at break
[0358] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength and elongation at break of three specimens were tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.
[0359] (4) 110-150℃ thermal shock
[0360] The test was carried out in accordance with Appendix A of GB / T 32129-2015, with a test temperature of 23±2°C and a weight of 2kg. Using the heat shock test device of Hebei Zhongke Beigong Testing Instrument Co., Ltd., three samples were tested at each temperature, and the results were averaged.
[0361] The test results are shown in Table 3.
[0362] Table 2 Examples of the present invention and comparative examples
[0363]
[0364]
[0365]
[0366] Table 3 Performance test table of the embodiments of the present invention and comparative examples
[0367]
[0368] According to Table 3, it can be seen that the polyether TPU and polyester TPU injection molding sheets of Examples 1-9 have good flame retardant properties, and the flame retardant grades all reach V0 level. When the V0 level is tested, there is no dripping, and the oxygen index is >25%, which shows that the TPU material of the present invention has good flame retardant properties. It can be seen from Examples 5, 6, and 8 that the polyether TPU and polyester TPU injection molding sheets have good flame retardant properties, and the flame retardant grades all reach V0 level. When the V0 level is tested, there is no dripping, and the oxygen index is >25%. At the same time, they have good mechanical properties, the tensile strength is >20MPa, the elongation at break is >500%, and the thermal shock of 110℃-150℃ does not crack, which shows that the TPU material of the present invention has good flame retardant properties and mechanical properties. It can be seen from Example 7 and Comparative Example 1 that the number of modified POSS flame retardant synergist 1 is too high, the flame retardant grade is V1, the flame retardant performance is not up to standard, the oxygen index decreases, the mechanical properties decrease, and the tensile strength and elongation at break are both reduced; It can be seen from Example 7 and Comparative Example 2 that when the modified POSS flame retardant synergist 1 is not added, the flame retardant grade is V2, there are drips, the flame retardant performance is not up to standard, the oxygen index decreases, and the tensile strength decreases; It can be seen from Example 7 and Comparative Example 3 that when the phosphorus-based flame retardant diethyl aluminum hypophosphite is not added, the flame retardant grade is V2, there are drips, the flame retardant performance is not up to standard, the oxygen index decreases, and the tensile strength decreases; It can be seen from Example 7 and Comparative Example 4 that when the nitrogen-based flame retardant melamine urate (MCA) is not added, the flame retardant grade is V2, the flame retardant performance is not up to standard, the oxygen index decreases, and the tensile strength decreases; Example 7 and Comparative Example 5 can It can be seen that when only modified POSS flame retardant synergist 1 is used as a flame retardant, the flame retardant grade is V2, the flame retardant performance is not up to standard, the oxygen index is reduced, and the tensile strength and elongation at break are both reduced; it can be seen from Example 7 and Comparative Example 6 that when only the phosphorus-based flame retardant diethyl aluminum hypophosphite is used, the flame retardant grade is V2, there are drippings, the flame retardant performance is not up to standard, the oxygen index is reduced, and the tensile strength is reduced; it can be seen from Example 7 and Comparative Example 7 that when only the nitrogen-based flame retardant melamine urate (MCA) is used, the flame retardant grade is V2, there are drippings, the flame retardant performance is not up to standard, the oxygen index is low, and the tensile strength and elongation at break are both reduced, which shows that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists have synergistic flame retardant effects with phosphorus-based flame retardants and nitrogen-based flame retardants, while reducing the amount of various flame retardants used, the flame retardant properties and mechanical properties of TPU materials are improved.It can be seen from Example 7 and Comparative Example 8 that the modified POSS flame retardant synergist 1 has improved anti-drip, oxygen index, tensile strength and elongation at break compared with the benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant; it can be seen from Example 7 and Comparative Example 9 that the modified POSS flame retardant synergist 1 has improved flame retardancy, anti-drip, oxygen index, tensile strength and elongation at break compared with the aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant; it can be seen from Example 7 and Comparative Example 10 that the modified POSS flame retardant synergist 1 has improved anti-drip performance compared with the flame retardant mixed with aminopropyl heptaisobutyl caged polysilsesquioxane and benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid. , oxygen index, tensile strength and elongation at break are all improved; it can be seen from Example 7 and Comparative Example 11 that the flame retardant grade, anti-drip performance, oxygen index and tensile strength of the modified POSS flame retardant synergist 1 are improved compared with the modified POSS flame retardant 3, i.e., the methyl boric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant; it can be seen from Example 7 and Comparative Example 12 that the flame retardant grade, anti-drip performance, oxygen index and tensile strength of the modified POSS flame retardant synergist 1 are improved compared with the modified POSS flame retardant 4, i.e., the phenyl boric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, which illustrates that the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists of the present invention have excellent flame retardant properties.
[0369] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A thermoplastic polyurethane elastomer material, characterized in that: The raw materials of the thermoplastic polyurethane elastomer material include, by weight: Thermoplastic polyurethane elastomer 70-90 parts, Phosphorus flame retardant 10-30 parts, 10-30 parts of nitrogen flame retardant, 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
2. The thermoplastic polyurethane elastomer material according to claim 1, characterized in that: The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
3. The thermoplastic polyurethane elastomer material according to claim 1, characterized in that: The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:
4. The thermoplastic polyurethane elastomer material according to claim 3, characterized in that: The molar ratio of compound 1 to compound 2 is 2:
1.
5. The thermoplastic polyurethane elastomer material according to claim 3, characterized in that: The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
6. The thermoplastic polyurethane elastomer material according to claim 1, characterized in that: The raw materials of the thermoplastic polyurethane elastomer material include, by weight: Thermoplastic polyurethane elastomer 70-90 parts, Phosphorus flame retardant 10-20 parts, 10-20 parts of nitrogen flame retardant, 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.
7. The thermoplastic polyurethane elastomer material according to claim 1, characterized in that: The thermoplastic polyurethane elastomer includes polyether type or polyester type thermoplastic polyurethane elastomer.
8. The thermoplastic polyurethane elastomer material according to claim 1, characterized in that: The phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide; And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.
9. The thermoplastic polyurethane elastomer material according to claim 1, characterized in that: The raw materials of the thermoplastic polyurethane elastomer material also include at least one of a lubricant, an antioxidant, an anti-hydrolysis agent, and a matting agent; wherein, the raw materials are calculated by weight, the lubricant is 0.5-1 part, the antioxidant is 0.5-2 parts, the anti-hydrolysis agent is 0.5-2 parts, and the matting agent is 2-10 parts.
10. A method for preparing a thermoplastic polyurethane elastomer material as claimed in claim 1, characterized in that: The method comprises the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder, and obtaining granular materials, namely the thermoplastic polyurethane elastomer material.
11. The method for preparing a thermoplastic polyurethane elastomer material according to claim 10, characterized in that: The raw materials also include at least one of a lubricant, an antioxidant, an anti-hydrolysis agent, and a matting agent; And / or, the extruder is a twin-screw extruder, the extrusion temperature is 160-180° C., and the screw speed is 150-170 r / min.
Citation Information
Patent Citations
Boric acid functionalized magnetic nano material and one-pot preparation method thereof
CN113663658A
Multifunctional polyhedral oligomeric silsesquioxane as well as preparation method and application thereof
CN116041705A